2008
DOI: 10.1021/jf072873j
|View full text |Cite
|
Sign up to set email alerts
|

Radioresistance of Salmonella Species and Listeria monocytogenes on Minimally Processed Arugula (Eruca sativa Mill.): Effect of Irradiation on Flavonoid Content and Acceptability of Irradiated Produce

Abstract: This work studied the radiation resistance of Listeria monocytogenes and Salmonella species and the effect of irradiation on leaf flavonoid content and sensory acceptability of minimally processed arugula. Immersion in ozone-treated water reduced the analyzed microorganisms by 1 log. L. monocytogenes and Salmonella were not isolated from samples. Samples of this vegetable were inoculated with a cocktail of Salmonella spp. and L. monocytogenes and exposed to gamma irradiation. D10 values for Salmonella ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(40 reference statements)
1
5
0
2
Order By: Relevance
“…On iceberg lettuce, Shigella flexneri had similar D 10 values than Salmonella, around 0.2 kGy. On arugula minimally processed salads, D 10 values for Salmonella were in the range between 0.15 and 0.2 kGy and those for L. monocytogenes were between 0.3 and 0.5 kGy (Nunes et al, 2008). Similar D 10 values were found for L. monocytogenes and Salmonella on peeled minicarrots, minimally processed cucumbers and sprouted seeds (Caillet et al, 2006b;Dhokane et al, 2006;Saroj et al, 2006).…”
Section: New Efficacy Data Available In Scientific Literaturesupporting
confidence: 62%
See 1 more Smart Citation
“…On iceberg lettuce, Shigella flexneri had similar D 10 values than Salmonella, around 0.2 kGy. On arugula minimally processed salads, D 10 values for Salmonella were in the range between 0.15 and 0.2 kGy and those for L. monocytogenes were between 0.3 and 0.5 kGy (Nunes et al, 2008). Similar D 10 values were found for L. monocytogenes and Salmonella on peeled minicarrots, minimally processed cucumbers and sprouted seeds (Caillet et al, 2006b;Dhokane et al, 2006;Saroj et al, 2006).…”
Section: New Efficacy Data Available In Scientific Literaturesupporting
confidence: 62%
“…However, for some products, such as lettuce leaves, doses should not exceed 0.5 kGy to avoid softening (Niemira et al, 2002). Some salad vegetables could nevertheless withstand higher doses (up to 4 kGy) without noticeable quality loss (Nunes et al, 2008). Higher treatments, 3-5 kGy, were proposed for powdered, dehydrated vegetables (Dong-Ho et al, 2002).…”
Section: Limitations To the Use Of Food Irradiationmentioning
confidence: 99%
“…Many authors have reported sensory quality data of irradiated leafy vegetables: Prakash et al () (lettuce), Kamat et al () (coriander), Zhang et al () (lettuce), Fan and Sokorai () (lettuce, cilantro, parsley, red cabbage, and spinach among other vegetables), Gomes et al () (spinach), Nunes et al () (arugula), Neal et al () (spinach), Fan and Sokorai () (lettuce), Fan and Sokorai () (spinach), and Fan et al () (lettuce and spinach), employing different methodologies, radiation doses, packaging, atmosphere and storage conditions which led to some different results. Nevertheless, those authors who evaluated spinach leaves agreed that irradiation up to 1 kGy did not impair sensory quality (Fan et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However these maximum values depend on the type of products and might modify with new, resistant cultivars (Zhu, et al, 2009). For example, some salad vegetables could resist up to 4000 Gy without physical-chemical damages and considerable quality loss (Nunes et al, 2008) whereas, for some products, such as lettuce leaves and apple fruit (Gala and Fuji variety) radiation doses should not exceed 600 Gy (Dionísio et al, 2009;Niemira et al, 2002).…”
Section: Fruits and Vegetablesmentioning
confidence: 99%